The design of the algorithm for opinion mining in the media discourse in English and Belarusian - Kazlova, Veranika V. (Journal of the Belarusian State University. Philology, 2020)
The article runs about the design of the algorithm for opinion mining in the media discourse in English and Belarusian. The algorithm is based on the vocabularies of linguistic units that mark opinions in the media discourse (733 units that are mentioned in more than 5000 opinionated contexts). The advantage of the proposed model lies in the fact that it considers the semantical meaning of the linguistic markers in both languages, their frequency, and the typology of opinionated passages in the context of automatic sorting of opinions. The algorithm includes a number of steps: the search of opinion markers based on the developed vocabularies of linguistic markers, the assignment of a certain «weight» to each sentence depending on the markers (by the sum of numeric values from the vocabulary; the article provides data on the «weight» of linguistic markers in a generalized form), then statements are divided into opinions-interpretations, opinions-theories, opinions-assumptions and an opinion’s combined type. The classification takes into account semantic and quantitative indicators.
Keywords: algorithm; opinion mining; vocabulary of linguistic markers; media discourse; automatic classification of opinions